Venomic, Transcriptomic, and Bioactivity Analyses of Pamphobeteus verdolaga Venom Reveal Complex Disulfide-Rich Peptides That Modulate Calcium Channels (2023)
Pamphobeteus verdolaga is a recently described Theraphosidae spider from the Andean region of Colombia. Previous reports partially characterized its venom profile. In this study, we conducted a detailed analysis that includes reversed-phase high-performance liquid chromatography (rp-HPLC), calcium influx assays, tandem mass spectrometry analysis (tMS/MS), and venom-gland transcriptome. rp-HPLC fractions of P. verdolaga venom showed activity on Ca V 2.2, Ca V 3.2, and Na V 1.7 ion channels. Active fractions contained several peptides with molecular masses ranging from 3399.4 to 3839.6 Da. The tMS/MS analysis of active fraction displaying the strongest activity to inhibit calcium channels showed sequence fragments similar to one of the translated transcripts detected in the venom-gland transcriptome. The putative peptide of this translated transcript corresponded to a toxin, here named ?-theraphositoxin-Pv3a, a potential ion channel modulator toxin that is, in addition, very similar to other theraphositoxins affecting calcium channels (i.e., ?-theraphotoxin-Asp1a). Additionally, using this holistic approach, we found that P. verdolaga venom is an important source of disulfide-rich proteins expressing at least eight superfamilies.